2020
DOI: 10.1175/jcli-d-19-0082.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lead Predictions of Warm Season Droughts in South Korea Using North Atlantic SST

Abstract: Understanding and predicting warm season (May–October) droughts is critically important in South Korea for agricultural productivity and water resource management. Using a 6-month standardized precipitation index ending in October (SPI6_Oct), we investigate the interannual variability of warm season droughts and the related large-scale atmospheric circulations for the most recent 20-yr period (1995–2014). Cyclonic (anticyclonic) circulations to the east of Japan (in the North Pacific) tend to induce warm seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…S1 – S2 ). This may be surprising given that some previous studies have shown these two factors to be good predictors of springtime rainfall over the Korean Peninsula (Myoung et al 2020 ), which is an important wet removal mechanism of PM 2.5 concentrations. Moreover, there are studies that find evidence of linkage between the first mode wintertime PM 10 concentrations over the Korean Peninsula and Arctic sea ice (Kim et al 2019 ; Lee et al 2020 ).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…S1 – S2 ). This may be surprising given that some previous studies have shown these two factors to be good predictors of springtime rainfall over the Korean Peninsula (Myoung et al 2020 ), which is an important wet removal mechanism of PM 2.5 concentrations. Moreover, there are studies that find evidence of linkage between the first mode wintertime PM 10 concentrations over the Korean Peninsula and Arctic sea ice (Kim et al 2019 ; Lee et al 2020 ).…”
Section: Resultsmentioning
confidence: 86%
“…4 ), with a hint of tripole-like SST mode in the North Atlantic including the area south of Greenland. The North Atlantic is known to influence East Asia through changes in atmospheric circulation that exhibit poleward and then equatorward wave trains (e.g., Ok et al 2017 ; Myoung et al 2020 ). In addition, due to the slowly varying nature of the ocean, the correlation patterns remain largely unchanged from September to November (i.e., 3 months ahead) through October–December (2 months ahead) and November to January (1 month ahead), suggesting that the equatorial Atlantic SST exerts a significant influence at seasonal time scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The year 2016 is characterized by a heatwave extreme in Korea with arid and hot weather (Figure 5a,c), which is also well described in Yeh et al (2018). Based on a statistical analysis by Myoung et al (2020), SST conditions over the Atlantic Ocean are associated with more precipitation in 2022 and less precipitation in 2016. However, this study does not fully explain extreme behaviour in both years, especially in August, because it is conducted in 6‐month averaged precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…A trend line is also presented if the p value of the slope is significant (< 0.10) based on student's t-test. South Korea has experienced a multiyear drought in 2014-2016 (Bae et al, 2019;Myoung et al, 2020). The dry period is properly represented in variations in the frequencies of the node (1,1), but is also manifested in other frequencies.…”
Section: Identified Spatial Patterns Of Streamflowmentioning
confidence: 99%